Price-sensitive demand and market entry - Yiquan Gu; Alexander Rasch; Tobias Wenzel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
This paper revisits the optimal entry decision in a differentiated product market where customer demand is price-sensitive and depends on a per-unit transport cost. We show that too few firms may enter for high entry cost and high transport cost compared to the socially optimal outcome.
Keywords: L11; L13; 330; Circular city; Horizontal product differentiation; Market entry; Price-sensitive demand